(untitled) (Impact: Journal of Transformation, 2020)
This paper looks at holistic transformative development for rural women which is church based. The study shows the historical development of diakonia, its disintegration from evangelical circles and how it has impacted the local context of Africa Inland Church (AIC). While it aims for the transformation of rural women’s contexts in Kenya. The paper thus takes a comparative approach with a Malawian case study to articulate holistic development. The specific context is Ebenezer, Kithuiani area in Kangundo Sub-County, Machakos. Modern negative attitudes toward marginalised rural women need to be re-shaped by the church. This approach amplifies social transformation and social change further into a holistic gospel paradigm. It interrogates how the mentioned disintegration affects social action and the church’s development agenda by comparing it with the Q Method in the Innovations for Poverty Action (IPA) program in Malawi.